Role of multimodality cardiac imaging in the management of patients with hypertrophic cardiomyopathy: an expert consensus of the European Association of Cardiovascular Imaging Endorsed by the Saudi Heart Association. - Cardim, N (2016)
Submitted by arminda sustelo (arminda.sustelo@hff.min-saude.pt) on 2016-03-29T14:16:23Z No. of bitstreams: 1 Eur Heart J Cardiovasc Imaging. 2015 Mar, 16(3) 280.pdf: 3567190 bytes, checksum: 1c521f7b0033a88184778625a91cecfd (MD5)